Lipid Metabolic Disorders and Ovarian Hyperstimulation Syndrome: A Retrospective Analysis - Liu, Feifei; Jiang, Qi; Sun, Xuedong; Huang, Yuzhen; Zhang, Zhenzhen; Han, Ting; Shi, Yuhua (Frontiers in Physiology, 2020)
Background: To evaluate the effect of abnormal lipid metabolism on the incidence of moderate and severe Ovarian hyperstimulation syndrome (OHSS) in the duration of assisted reproduction techniques (ART). Methods: The study included 233 moderate or severe OHSS patients after receiving in-vitro fertilization-embryo transfer(IVF-ET) or intracytoplasmic sperm injection(ICSI). They were divided to two groups according to the presence or absence of abnormal lipid metabolism to evaluate whether abnormal lipid metabolism can develop the severe OHSS.Subgroup analysis was set to avoid deviation.The main outcome measures included the incidence of moderate OHSS and severe OHSS, total dose of gonadotrophin(Gn), number of retrieved oocytes, age and body mass index(BMI). Results: In the untransplanted groups, the ones with abnormal lipid metabolism are more likely to develop to severe OHSS presenting more serious clinical manifestations (P<0.05), while the incidence of severe OHSS among transplanted groups had no statistical significance(P>0.05). The rate of OHSS development was significantly higher in the patients who received fresh cycle embryo transfers comparing to the frozen-thawed embryo transfers (P<0.05). Conclusions: Our study results suggested that patients with OHSS combined with abnormal lipid metabolism who received embryo transfers at once after controlled ovarian hyperstimulation have a higher chance of developing to severe OHSS. It is essential to consider the risk of occurrence of OHSS in patients with abnormal lipid metabolism required fresh embryo transfers.